Accumulation of Cav3.2 T-type Calcium Channels in the Uninjured Sural Nerve Contributes to Neuropathic Pain in Rats with Spared Nerve Injury - Chen, Wen; Chi, Ye-Nan; Kang, Xue-Jing; Liu, Qing-Ying; Zhang, Hao-Lin; Li, Zhi-Hua; Zhao, Zi-Fang; Yang, Yin; Su, Li; Cai, Jie; Liao, Fei-Fei; Yi, Ming; et al. (Frontiers in Molecular Neuroscience, 2018)
Injuries to peripheral nerve fibers induce neuropathic pain. But the involvement of adjacent uninjured fibers to pain is not fully understood. The present study aims to investigate the possible contribution of Cav3.2 T-type calcium channels in uninjured afferent nerve fibers to neuropathic pain in rats with spared nerve injury (SNI). Aβ-, Aδ- and C-fibers of the uninjured sural nerve were sensitized revealed by in vivo single-unit recording, which were accompanied by accumulation of Cav3.2 T-type calcium channel proteins shown by Western blotting. Application of mibefradil, a T-type calcium channel blocker, to sural nerve receptive fields increased mechanical thresholds of Aβ-, Aδ- and C-fibers, confirming the functional involvement of accumulated channels in the sural nerve in SNI rats. Finally, perineural application of mibefradil or TTA-P2 to the uninjured sural nerve alleviated mechanical allodynia in SNI rats. These results suggest that axonal accumulation of Cav3.2 T-type calcium channels plays an important role in the uninjured sural nerve sensitization and contributes to neuropathic pain.